Understanding Why People Enjoy Loud Sound - Welch, David; Fremaux, Guy (Seminars in Hearing, 2017)
Sounds at levels that can injure the ear are regarded as enjoyable by many people. In many societies, a common form of this behavior is listening to loud music, either via personal audio systems or at music venues. Drawing on theory from the literature around loud sound and emotional responses to music, and combining it with concepts of physiological sound adaptation and classical conditioning, we developed a model of the process that may underlie people's enjoyment of loud sound, particularly loud music in nightclubs. The Conditioning, Adaptation, and Acculturation to Loud Music (CAALM) model proposes that the benefits associated with loud sound, alongside other desirable aspects of nightclubs, provide the unconditioned stimuli. Over time regular clubbers become conditioned to enjoy loud sound in itself. Exposure to loud sound also causes adaptation within the auditory system, so there is both a desire for, and tolerance of, loud sound during leisure time. This sets up an expectation of loud music as a cultural norm, and staff of leisure venues, who are themselves part of that culture, set music levels to meet customer expectations; and a cycle is perpetuated. This theory may be a useful consideration for health promotion and hearing conservation interventions.
Keywords: Loud; music; adaptation; noise-induced hearing loss; conditioning